2008
DOI: 10.1177/0272431608314662
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Response Styles Theory and the Hopelessness Theory of Depression in Preadolescents

Abstract: This study compares predictions from the Hopelessness Theory of depression (Abramson, Metalsky, & Alloy, 1989) with the Response Styles Theory of depression (RST; Nolen-Hoeksema, 1987) with data obtained from a preadolescent sample (ages 9 to 13 years). Three hundred ten preadolescents completed self-report measures of stress, sense of control, rumination, and depressive symptoms. Neither rumination nor perceived control moderated the relationship between stress and depressive symptoms. However, path models re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…Thus, ruminative adolescents may be particularly reactive to the depressive effects of dependent familial stressors (e.g., conflict) and difficulties with peers that threaten social relationships. Our findings may help to account for discrepancies among previous studies that only have examined negative life events as a unitary construct, and that have not found support for vulnerability-stress models of rumination in adolescence (Abela et al, 2009; Jose & Brown, 2008; Rood et al, 2012; Weir & Jose, 2008). This finding is in contrast to a recent study by Cox et al (2011), which found that rumination interacted with dependent and independent stressors, but not interpersonal stressors, to predict depressive symptoms.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Thus, ruminative adolescents may be particularly reactive to the depressive effects of dependent familial stressors (e.g., conflict) and difficulties with peers that threaten social relationships. Our findings may help to account for discrepancies among previous studies that only have examined negative life events as a unitary construct, and that have not found support for vulnerability-stress models of rumination in adolescence (Abela et al, 2009; Jose & Brown, 2008; Rood et al, 2012; Weir & Jose, 2008). This finding is in contrast to a recent study by Cox et al (2011), which found that rumination interacted with dependent and independent stressors, but not interpersonal stressors, to predict depressive symptoms.…”
Section: Discussioncontrasting
confidence: 50%
“…Because adolescent girls often experience puberty and this associated cognitive development earlier than boys, when ruminating, early adolescent girls may be able to more thoroughly consider the negative causes and consequences of stressful events in their lives, which may precipitate or exacerbate dysphoric mood. Consistent with this hypothesis, one study found that the rumination-stress interaction predicted depressive symptoms among 7-to-14 year old girls, but not among boys, but other studies either have found no sex differences in the rumination-stress interaction (Abela & Hankin, 2011; Rood et al, 2012; Weir & Jose, 2008) or have not reported sex differences in this interaction (Cox et al, 2011; Hankin, 2009). Moreover, no study has evaluated sex differences in the rumination interaction with various stress subtypes.…”
Section: Can Response Styles and Stress Account For The Emerging Sex mentioning
confidence: 92%
See 1 more Smart Citation
“…The Response Style Questionnaire (RSQ; Nolen-Hoeksema & Morrow, 1991) is a commonly used measure of child and adolescent rumination and distraction coping styles (Kercher & Rapee, 2009;Schwartz & Koenig, 1996;Weir & Jose, 2008). In the current study, we used the 17 items identified by Bagby and Parker (2001) as loading onto a symptom-focused factor and a self-focused rumination factor, which together constitute the Rumination Response Scale (RRS).…”
Section: Wave 1 (Preflood) Measuresmentioning
confidence: 99%
“…The present research treated them as mediators, and another analysis of Study 2's data (Weir & Jose, 2008) succeeded in demonstrating that OSOC scores functioned as a mediator between stress and depression, and also between rumination and depression. But it remains to be seen whether these constructs of control will also operate as a moderator in particular situations.…”
Section: Future Directionsmentioning
confidence: 67%